2013
DOI: 10.1007/s00382-013-1728-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct quasi-biweekly features of the subtropical East Asian monsoon during early and late summers

Abstract: Using Global Precipitation Climatology Project daily rainfall and ERA interim reanalysis data, we investigate the distinct characteristic of quasi-biweekly variation (QBV: 12-20 days) over East Asia (EA) during early (June 10-July 20) and late (July 21-August 31) summer. The QBV maximum variance is found over the core region of EA (30°-40°N, 110°-130°E), which includes eastern China (lower reaches of the Yellow, Huaihe, and Yangtze rivers) and the Korean Peninsula. At both its peak wet and dry phases, QBV over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…The YHRB rainfall shows obvious 20-50-, 21-30-, and 12-20-day (quasi biweekly) periodical variations as a response to the intraseasonal variations over subtropical and mid-to high-latitude regions Mao et al 2010;Yang et al 2010Yang et al , 2013. In addition, many of the flooding rainfall events over YHRB are associated with the extremely active phase of intraseasonal variations.…”
Section: Introductionmentioning
confidence: 95%
“…The YHRB rainfall shows obvious 20-50-, 21-30-, and 12-20-day (quasi biweekly) periodical variations as a response to the intraseasonal variations over subtropical and mid-to high-latitude regions Mao et al 2010;Yang et al 2010Yang et al , 2013. In addition, many of the flooding rainfall events over YHRB are associated with the extremely active phase of intraseasonal variations.…”
Section: Introductionmentioning
confidence: 95%
“…They considered the abrupt changes of mean state in mid to late July, which includes the northward migration of westerly jet, South Asia High (SAH) and WPSH, and the weakening and broken of westerly jet, are the root causes of the change in behavior of quasi-biweekly variability (QBV). Yang et al (2014) also indicated that the tropical monsoon trough and midlatitude westerly jet were the possible sources of QBVover subtropical EA in both subseasons and were useful to provide guidance for 2-3-week predictions over the EA. In our study, we have conducted preliminary analysis on how the WPSH influence the QBWO during summer.…”
Section: Preliminary Analysismentioning
confidence: 99%
“…In general, the intensity and coverage of the WPSH may play crucial roles in modulating the occurrence and characteristics of the convection and further impact the evolution and propagation of the QBWO over the SCS. Yang et al (2014) found the differences of quasibiweekly characteristics over EA at early (June 10-July 20) and late (July 21-August 31) summer. They considered the abrupt changes of mean state in mid to late July, which includes the northward migration of westerly jet, South Asia High (SAH) and WPSH, and the weakening and broken of westerly jet, are the root causes of the change in behavior of quasi-biweekly variability (QBV).…”
Section: Preliminary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a member of the Asian summer monsoon system, the SAH's spatiotemporal variability and impacts on the weather and climate over Asia and beyond have been investigated (Zhang et al 2002(Zhang et al , 2005(Zhang et al , 2016Liu et al 2004Liu et al , 2007Liu et al , 2013Duan and Wu 2005;Randel and Park 2006;Zarrin et al 2010;Huang et al 2011;Jiang et al 2011;Qu and Huang 2012;Wei et al 2014;Yang et al 2014;Ren et al 2015;Wu et al 2015;Chen and Zhai 2016;Shi and Qian 2016;Yang and Li 2016). Especially, variations of the SAH on subseasonal time scale have attracted more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%